Re-Presentation and Re-Memory of the Southern Landscape in Cane : Jean Toomer’s Memorial Minor Writing - Christine Dualé (Babel: Littératures Plurielles, 2019)
In Cane, Jean Toomer’s poems, sketches and songs are images of nature and cities, of rural and urban environments. Cane is a landscape conceived and designed by a man who struggled for understanding and is about a man’s own perceptions of Black life in the South. By focusing on some of the poems and sketches we will see how Toomer, by appropriating the language, linked life and work to unveil the memory and truth of the Southern landscape. Toomer provided multiple entries into his text, a characteristic of “minor literature” as exposed by Gilles Deleuze and Félix Guattari in Mille Plateaux. Thus, we will try to assess the variability of interpretations of Toomer’s text through his writing and re-memory of the South.